Evaluación de exposición de riesgos laborales en espacios confinados de los tanques de almacenamiento de combustible de la aeronave Boeing 737-200/300/400/500 en la Dirección de la Industria Aeronáutica del Ecuador OMA-DIAF. - Pacheco Cajas, Alba Selena (2020)
This project "Evaluation of Occupational Hazards Exposure in confined spaces of fuel storage tanks of the Boeing 737-200 / 300/400/500 aircraft at the Directorate of the Aeronautical Industry of Ecuador OMA-DIAF" raises the identification of occupational hazards, through risk management, with the proposal of alternatives to perform safe working in confined spaces, specifically in fuel tanks. In the process, field observation, descriptive research, bibliographic sources, data collection, techniques and measurement tools such as: Volatile Organic Compounds (VOCs) were applied for the evaluation of controlled risks. This prepares an analysis of the current situation in which one works within the company. Once the risks were identified and evaluated by means of the INSHT General Risk Assessment Method in different activities, a safe working procedure was designed where the sequential way of actions necessary for safe execution of the entrusted tasks is proposed. Based on obtained results, it is concluded that the confidence of the technicians will increase, as well as the prevention of accidents and occupational diseases that are currently in the Directorate of the Aviation Industry of FAE is a critical problem.